Supercritical fluids state of CO2 and its the technological performance - NR Barakaev; MT Kurbonov; BT Mukhamadiev; Fayzullayev Asqar (Archive of Biomedical Science and Engineering - Peertechz Publications, 2021)
The prospect considered of the using Super Critical Fluids (SCF) for extraction fat, ethereal oil from seed grape. Possibility of the use is shown for this and its problems bound by accessibility of the high-priced equipment. In the last decennial event in developed country of the world is actively developed problem of the rational use material in supercritical condition in closing technological cycles and the other high technology. One of the decisions given problems is a using as extract liquefied carbon dioxide. In the world spreads exactly CO2 extraction. This is bound in the first place with that that this process highly profitable, more technological, allows to produce the conversion not only high-quality cheese, but also departure production for the reason extraction of them main component for giving more high quality low sort of the product. The Extraction by carbon dioxides in liquefied condition greatly increases the spectrum selected biologically active join, as well as allows to get such concentrations biologically active material in final product, which impossible get nor one of other known methods of extractions.